NILAI PENTING SUMBERDAYA ARKEOLOGI BAGI DAERAH - Susanto, Nugroho Nur (Naditira Widya, 2007)
As one of cultural heritage, archaeological site have several significant values. In Kalimantan Selatan, and general of Kalimantan.: east Kalimantan and center of Kalimantan some prominent significant values are as educational media and generally as tourism destination location, local icons, increase social solidarity and integration. The significance of archaeological sites can be managed to increase local income. It is argued that we should pay more attention to local archaeological resources and preserve it. This is because preservation of archaeological resource can influence the idea of local culture, political and academical policy Archaeological sites in Kalimantan Selatan and Kalimantan of generally also have an important role to promote Kalimantan provinces to our public .